2017
DOI: 10.1007/s11906-017-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Angiotensin-Converting Enzyme: the Old and the New

Abstract: Purpose of Review The intrarenal renin-angiotensin-aldosterone system (RAS) is an independent paracrine hormonal system with an increasingly prominent role in hypertension and renal disease. Two enzyme components of this system are angiotensin-converting enzyme (ACE) and more recently discovered ACE2. The purpose of this review is to describe recent discoveries regarding the roles of intrarenal ACE and ACE2 and their interaction. Recent Findings Renal tubular ACE contributes to salt-sensitive hypertension. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 61 publications
0
31
0
5
Order By: Relevance
“…Meanwhile, biochemical and cell-based assays can be established to screen chemical compound libraries to identify novel inhibitors. On the other hand, many ACE inhibitors are currently used to treat hypertension and other cardiovascular diseases [25]. Among them are captopril, perindopril, ramipril, lisinopril, benazepril, and moexipril.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, biochemical and cell-based assays can be established to screen chemical compound libraries to identify novel inhibitors. On the other hand, many ACE inhibitors are currently used to treat hypertension and other cardiovascular diseases [25]. Among them are captopril, perindopril, ramipril, lisinopril, benazepril, and moexipril.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, at the concentration of 20 µg/mL, pGlu was found to inhibit 98.2 % of the activity of human ACE in vitro. ACE plays a central function of converting angiotensin (Ang ) to Ang and it has been shown to contribute to hypertension via the reninangiotensin system (RAS) [21][22][23]. However, the circulating and intrarenal RAS was supposed to be downregulated to compensate the up-regulated local uteroplacental RAS in preeclampsia [24,25].In our study, we found that the serum pGlu was increased in PE group with a fold-change value of 1.3, which may be associated with the downregulation of intrarenal RAS in preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Более того, один из важных механизмов действия иАПФ -ингибирование реабсорбции натрия. В свою очередь, реабсорбция натрия рассматривается как пусковой фактор повышения АД у солечувствительных больных, регулируемый интраренальной РААС [20,21]. Вероятно, применение иАПФ вечером может сопровождаться и натрийуретическим эффектом, способствовать уменьшению объем-зависимой нагрузки на миокард и регрессу структурно-функциональных изменений ЛЖ.…”
Section: Discussionunclassified